Development of starter culture for the production of Degue, a West African traditional fermented milk product - Abormegah, Leonardo (University of Cape Coast, 2019)
Burkina is a milk/millet product which has suddenly become popular in Ghana in the last few years. The product is thought to have originated from Burkina Faso but Burkina is unknown in that country. Rather Degue, a Fulani fermented milk product containing millet is well known in West African Sahelian countries including Burkina Faso. This work was carried out to compare the burkina and Degue processes, and develop a starter culture for the production of Burkina/ Degue in Ghana. A survey was carried out on Burkina producers and consumers in Accra, and fermenting milk samples collect on separate occasions from two original degue producers in Accra. Burkina was found to be the same as Degue based on the processing procedure except that producers in Ghana used reconstituted powdered milk whilst Degue producers in Sahelian countries use fresh cow milk. The spontaneous fermentation which occurs during Degue production was found to be a lactic acid fermentation and the population of LAB increased by 4 log units to about 8 log 10 CFU/ml during 24 h of fermentation. Percentage titratable acidity increased from 0.14 to 0.72% during fermentation whilst the pH values dropped from about 6.5 to 4.12. Lactic acid bacteria species identified in the spontaneous milk fermentation were Lactobacillus plantarum (43.75%), Lactobacillus delbrueckii ssp. lactic (31.25%), Lactobacillus brevis (18.75%), and Lactobacillus buchneri (6.25%). The LAB were identified by their pattern of carbohydrate fermentation and also by MALDI-TOF Mass Spectrometry which is based on the analysis of protein spectrum from bacterial ribosome. Both methods gave the same species of LAB. For the development of starter culture, isolates of the lactic acid bacteria were used to inoculate pasteurized milk either singly or in combinations and the rate of acidification determined. Antimicrobial activity of the isolates against Staphylococcus aureus, Escherichia coli 0157; H7, Salmonella typhimurium and Listeria monocytogenes were also determined as well as survival of the pathogens in milk inoculated with the isolates. Production of amylase and exopolysaccharides by the isolates were also determined. In sensory testing, Degue produced using the different isolates were evaluated by a sensory panel. For overall acceptability in the consumer preference test, the panellists ranked Degue fermented with Lb. delbrueckii ssp lactis and also Degue fermented with Lb. brevis first with an average score of 7.35 each which corresponded with the products being liked moderately, followed by Lb. plantarum (6.83), Lb. buchneri (6.45), spontaneously fermented Degue (5.98), and lastly Degue fermented with a combination of Lb. delbrueckii ssp lactis and Lb. plantarum (5.90). However, the frequency with which Lb. delbrueckii- Degue was picked as the best product by panellists was 16 hence Lb. delbrueckii ssp lactis was selected as the starter culture for producing Degue in Ghana.
xiv,141p:,ill
Keywords: Degue; Fermentation; Lactic Acid Bacteria; Starter Culture; Technological Properties; Traditional Femented Foods